Program Perancangan Kegiatan Kredit Mikro (Dana Bergulir) Bagi Mahasiswa di Perguruan Tinggi - Lasmi, Lasminasih (Faculty of Economic and Business, 2015)
Design Program of Microcredit Activity (Revolving Fund)For Students in Higher Education. Systems design of microcredit is generally conducted by financial institutions of which credit is mostly provided for private sectors, both large and small medium Enterprises (SMEs). However, credit for new entrepreneurs, especially for college students, who want to start a business has never been provided formally due to numerous factors and among others is because of the absence of collateral. Meanwhile, in order to stimulate the eagerness of running a business, credit is inevitably essential. Hence, this study is proposing a comprehensive systems design to overcome any potential problems between new entreprenurs in getting credit from financial intitutions. This systems design handles a series of processes in granting credit which starts from screening and selecting business proposals. When the proposals are accepted and the credit is granted, then they will get processes of mentoring, training, exhibition and finally process of monitoring through financial reports. Also there will be internet facility of integrated microcredit information system to ease communication between the new entrepreneurs, mentors and financial institutions. This systems design can enhance success for the new entrepreneurs and diminish any potential risks of unable to repay the credit. So when the business starts to grow, they can apply for bigger credit.DOI: 10.15408/ess.v5i1.2329